A survey of the relevance and effectiveness of the library catalogue: the case Kenneth Dike Library. (1999)
As libraries in Nigeria step into the age of Information Technology just like other libraries the world-over, an inventory of the use of manual system of information retrival is surveyed with Kenneth Dike Library, University of Ibadan as a case study. The survey, which is to ascertain the relevance and effectiveness of the use of card catalogue as means of information retrieval, reveals a general lack of understanding of its use. A non-challant attitude to Library Orientation is shown. A quiet sense of joyful expectancy and a mild hesitant sense of apprehension towards a full-blown computerisation of the library catalogue is revealed. This paper suggests a re-orientation in the attitude of students towards library orientation programmes such that their interest in the programmes could be rekindled while recommending that there should be continued instruction, all the year through, on library use at the Main and Faculty Library levels, preparatory to the introduction of On-line Public Acess Catalogue (OPAC)